Methodology for management LAN network security standards-based heterogeneous - Karma Rosas Paredes (2019)
Currently, telecommunications and informatics are constantly influenced by technological, advances,competition is strong general mobility, networks convergence, different protocols and services, IP as suport service, software dependence, and others. They result in heterogenous networks also called new generation networks (NGN).There are no working norms for managing security in modern telematics networks . there are no standards for NGNS . Our main objective is to develop a method for administering security base on standards, so that securiy tasks are ordered in NETWORKS organizing security tasks in planning, implementation, management, verification and security support.The perspective for this study is for different technologies in lan networks in the range of medium and large networks, that have 4 layers and can be validated, it may allow this NETWORKS get any,international certification for their operativeness